Pengembangan Bahan Ajar Digital 3d Page Flip Menggunakan Discovery Learning pada Materi Alkohol - ST. Nurfajariayatin ST. Nurfajariayatin; Mohammad Masykuri; Lina Mahardiani (Universitas Sebelas Maret, 2025)
Alcohol and Ether are materials that have the characteristics of abstract chemical concepts and many concepts that must be understood by students as well as the lack of students' ability to relate them to everyday life. The development of 3D page flip digital teaching materials based on discovery learning is an effective learning instrument to improve students' critical thinking skills and can increase students' independence to better recognize chemistry in everyday life. This study aims to develop 3D page flip digital teaching materials based on discovery learning on alcohol and ether materials. 3D page flip professional is an application used to create E-Books, E-Magazines, E-Papers and others. 3D page flip professional software can add videos, images, audio, hyperlinks and multimedia objects. The use of professional 3D page flip in the form of a digital book version is able to assume readers on a Personal Computer (PC) or other gadget devices such as Android. The type of research used is development research using the research and development method by adopting the Four-D development model to measure students' critical thinking abilities. The results of the development of 3D page flip digital teaching materials obtained a feasibility value from material experts with an average value of 4.400 on a scale of 5, the feasibility value from media experts had an average value of 4.225 on a scale of 5 and was tested on class XI students at SMA Batik 1 Surakarta who had an average value in the control class of 63.60 and in the experimental class of 77.10. This shows that the 3D page flip digital teaching materials based on discovery learning that were developed are suitable for implementation in schools